Individualizing hyperosmolar therapy for management of intracranial hypertension - Shrestha, Gentle Sunder (Journal of Society of Anesthesiologists of Nepal, 2018)
Intracranial hypertension is a major cause of morbidity and mortality in patients with brain injury. If not appropriately treated, it can precipitate brain ischemia, brain herniation and death. Hyperosmolar therapy remains the main armamentarium for management of raised intracranial pressure, especially in patients with diffuse lesions and where surgical options are not applicable. Substantial amount of studies have tried to explore the superiority of hypertonic saline or mannitol over the other. Due to significant heterogeneity in the pathophysiology of patients, variation in treatment threshold, method of drug administration and drug concentration, substantial evidence is lacking to support one agent over other. Hypertonic saline may be more effective than mannitol for lowering raised intracranial pressure. Well designed novel trials need to try to find the answer. Clinical, pathophysiological and biochemical data should be incorporated at bedside while individualizing selection of hyperosmolar therapy, with the aim to improve outcome and minimize harm. Journal of Society of Anesthesiologists of Nepal Vol. 4, No. 2, 2017, Page: 54-56